Analysis of General French Language Question Papers for the Third Intermediate Grade in Iraq Based on Bloom’s Taxonomy - Abbood Shareef Al-Turfi, Dijla ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study aims to analyze the general French language exams for third grade in Iraq. To fulfill this, two checklists were prepared. The first one is concerned with general shape criteria while the other one concerned with the six levels of the cognitive domain of revised Bloom’s taxonomy. The validity and reliability of two checklists were ensured. The results showed that the question setters have paid attention to layout and general shape criteria. Moreover, they revealed a balance within the distribution of questions across the lower levels of the cognitive domain. Also, it was found that the ratio of objective to subjective questions was suitable for this age grade. Furthermore, the abundance of understanding level question gave the students an advantage of lack of accreditation on rote memorization of the study material. Further works were suggested for future research. DOI: https://doi.org/10.54633/2333-024-057-006